EKSISTENSI AKSARA JAWI Nilai Keagamaan dalam Naskah Hikayat Iblis dan Nabi - Moh. Iqbal Nafi (Qurthuba: The Journal of History and Islamic Civilization, 2023)
Abstract: This article discusses religious studies in the Tale of the Devil and the Prophet which uses Jawi script and Malay. The aim of this article is to explore the treasures of the Jawi script in the content of the saga. The research in this article uses philological and historical methods. This article contains the results that the Jawi script can be said to have existed before 1303 AD, because there was a discovery of a stone with letters in Terengganu which read 22 February 1303 AD. Then, in analyzing the text in the saga of the Devil and the Prophet, elements of religious values such as alms, reading the Koran, fasting, and Hajj.